PERANCANGAN ALAT PERMAINAN EDUKATIF TERTIB BERLALU LINTAS UNTUK ANAK USIA 4-6 TAHUN - Kristina, Nathalia
Mobilization independence in traffic is one of the main moral education that needs to be instilled in children as early as possible. Based on the development of motor skills and cognitive abilities, children aged 6-8 years should be able to move around independently in traffic. However, in Indonesia, there are still many children aged 6-8 years who are not independent and still rely on their parents' help even for short distances. Therefore, this research is aimed at designing a product that can improve children's independence in traffic, including their desire and ability to walk to nearby destinations, use public transportation, and perform other activities in traffic without the need for parental guidance. This research uses a qualitative descriptive method with field observation, interviews with various parties, literature and precedent studies. The Educational Game Tool that will be designed is a set of products equipped with various features and supporting components that can be used both at home and in traffic as an educational medium and provide new experiences in traffic. These features include: • Educational cards, counters, and magnetic boards to optimize the child's experience throughout their journey in traffic. • Danger alarms and GPS that are connected to the parents' device as a safety system for the user. Furthermore, it is expected that this Educational Game Tool can also encourage children's desire, ability, and confidence to explore the city